Fluidity, Phenotype and Afro-Latin Group Consciousness. (July 2020) - Johnson, Marcus
Abstract: Racial fluidity and mixed phenotype have been posited as critical barriers to politicized black identity in the region. Using an original, survey experiment in Panama, this paper finds that racial fluidity and phenotype significantly affect who identifies as black, but have relatively little impact on the strength of measures of black group consciousness. Rather than reducing the strength of group consciousness all together, racial fluidity and phenotype influence the salience of different measures of group consciousness. Afro-Panamanians with phenotypic features that stably predict black self-identification express stronger beliefs that racial discrimination is a problem in Panama (perceived discrimination) and greater dissatisfaction with the social standing of their in-group (polar power). In contrast, Afro-Panamanians with mixed phenotypic features express stronger in-group affect (pride), stronger belief in the efficacy of black collective mobilization (collective efficacy), and stronger linked fate.